2017
DOI: 10.1007/s13659-017-0130-1
|View full text |Cite
|
Sign up to set email alerts
|

New Azulene-Type Sesquiterpenoids from the Fruiting Bodies of Lactarius deliciosus

Abstract: In the 1H NMR-guided fractionation of extracts from the edible mushroom Lactarius deliciosus, two new azulene-type sesquiterpenoids, 7-isopropenyl-4-methyl-azulene-1-carboxylic acid (1) and 15-hydroxy-3,6-dihydrolactarazulene (2), together with seven known compounds were characterized. Their structures were determined on basis of spectroscopic evidence, as well as by comparing with literature data. Amongst the known metabolites, the 13C NMR assignment of 15-hydroxy-6,7-dihydrolactarazulene (3) is reported here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…For instance, a PTP1B inhibitor, (24E)-3,4-seco-cucurbita-4,24-diene-3-hydroxy-26,29-dioic acid, is extracted from the sporocarps of Russula lepida , and has potential uses in treating type-2 diabetes and obesity 1 . Metabolites of many Lactarius species have potential antitumor and antiviral activities 2 . Auricularia auricula polysaccharides were reported to have potent antioxidant activities against hydroxyl and superoxide radicals 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a PTP1B inhibitor, (24E)-3,4-seco-cucurbita-4,24-diene-3-hydroxy-26,29-dioic acid, is extracted from the sporocarps of Russula lepida , and has potential uses in treating type-2 diabetes and obesity 1 . Metabolites of many Lactarius species have potential antitumor and antiviral activities 2 . Auricularia auricula polysaccharides were reported to have potent antioxidant activities against hydroxyl and superoxide radicals 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sesquiterpenoid compounds having an azulene skeleton were identified in L. deliciosus. One of the compounds, 7-acetyl-4-methylazulene-1-carbaldehyde, was found to show antibacterial activity against S. aureus [118]. Another azulene derivative, 7-acetyl-4-methylazulene-1-carboxylic acid, was detected in Lactarius salmonicolor [115].…”
Section: Azulenesmentioning
confidence: 99%
“…Owing to its excellent taste, texture, and flavor, L. deliciosus is popular in China, with some chemical substances and bioactivities of L. deliciosus being reported. Research has shown that sesquiterpenoids contribute to the unique color of L. deliciosus , some of which possess potent biological activities such as antimicrobial and anticancer [10,11,12]. Ding et al and Hou et al reported that L. deliciosus polysaccharides exhibited significant anti-tumor activity in mice in vivo and immunomodulatory effects through proliferative growth of both B cell and macrophages cell in vitro [13,14].…”
Section: Introductionmentioning
confidence: 99%